2007
DOI: 10.1051/0004-6361:20077153
|View full text |Cite
|
Sign up to set email alerts
|

Sydney observatory Galactic survey

Abstract: Context. First Epoch astrometric and radiometric information of a survey in the optical along the Galactic fourth quadrant is archived for further analysis in the time-domain. Aims. A photographic survey of 1.9 × 10 6 stars down to B-magnitude 14 ± 0.5 along the galactic meridian l = (330 ± 5)• , −64• ≤ b ≤ −7• and along the galactic equator 272• , is provided from century old astrographic plates of Sydney Observatory. Stellar candidates to investigate the Galaxy disk kinematics up to a distance of 1 kpc from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…Other two attempts to measure the distance from photometry are available from Fresneau et al (2007) and Pickles & Depagne (2010) they obtained 56 pc (no error bars) and 77 +50 −22 pc respectively. Our best SED fit yields 4700 K, in agreement with Ammons et al (2006), but our best spectrum fit is between K0V-K2V.…”
Section: Rejected Multiple Systemsmentioning
confidence: 99%
“…Other two attempts to measure the distance from photometry are available from Fresneau et al (2007) and Pickles & Depagne (2010) they obtained 56 pc (no error bars) and 77 +50 −22 pc respectively. Our best SED fit yields 4700 K, in agreement with Ammons et al (2006), but our best spectrum fit is between K0V-K2V.…”
Section: Rejected Multiple Systemsmentioning
confidence: 99%
“…7 the numbers of foreground stars (those with μ ≥ 0.02 yr −1 ) and background stars (μ ≤ 0.02 yr −1 ) as a function of the (B − V) 0 colour derived using our calibration (B − V) 0 = 0.26 + 0.82(m b −V). We note that Fresneau et al (2007) found no colour effect when deriving p.m. at the level of 0.002 yr −1 by comparing century-old astrographic observations and second-epoch Schmidt telescope ones used in the GSC 1.2 construction. While that result was based on Tycho-2 stars (Hog et al 2000) brighter than m b = 12 (Fresneau et al 2005), we presume it is valid for even fainter stars, and hence no severe systematic effect has been introduced into the data by our proper motion determinations.…”
Section: Validity Of the Rpmd For Stellar Group Classification In Sogsmentioning
confidence: 77%
“…The effect of the los-velocity on w depends on sin b, and our stellar sample along the galactic meridian verifies |b| ≤ 64 • , indicating that the los-velocity needs to be on the order of 75 km s −1 to have an effect on w of 50 km s −1 . We also restrict the analysis to stars with z ≤ 100 pc (a sample of 29 × 10 3 VSC stars), where a thin disk crossing effect has previously been detected (Fresneau et al 2007). Figure 14 shows the trends of σ 1 , σ 2 , and σ 3 as a function of dynamical time t. We observe that, while the σ 3 relation is relatively flat, σ 1 and σ 2 show the same upturn for t ≤ 1 Myr.…”
Section: Construction Of a Power-law For A Scattering Process With A mentioning
confidence: 90%
See 2 more Smart Citations